2016
DOI: 10.1109/jphot.2016.2553846
|View full text |Cite
|
Sign up to set email alerts
|

Diode-Pumped Nd:YAP Intracavity Optical Parametric Oscillator Emitting at 1603 nm: Influence of Energy-Transfer Upconversion

Abstract: A diode-end-pumped actively Q-switched Nd:YAP laser at 1080 nm is originally designed to intracavity pump a Potassium Titanyl Phosphate KTiOPO4 (KTP)-based optical parametric oscillator for obtaining the signal wavelength at 1603 nm. Under an absorbed pump power value of 11 W, the maximum average output power at the eye-safe radiation is efficiently generated to be 1.11 W at a pulse repetition rate of 10 kHz. At a pulse repetition rate of 5 kHz, the shortest pulse duration, the largest pulse energy, and the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…[6][7][8][9][10][11][12] In addition, the output wavelength of NCPM KTA-OPO varies with the tuning fundamental wavelength. 3,13) In 2011, Bai et al demonstrated a NCPM KTP-OPO emitting at 1.8 µm derived by a Nd:YAG=SrWO 4 Raman laser at 1180 nm. 14) In 2013, a 1625 nm signal light emitted from a NCPM KTA-OPO driven by a 1091 nm KTA Raman laser was obtained by Huang et al 15) In the same year, our group obtained a 2.1 µm NCPM KTA-OPO derived by a 1.3 µm Nd:YVO 4 laser.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In addition, the output wavelength of NCPM KTA-OPO varies with the tuning fundamental wavelength. 3,13) In 2011, Bai et al demonstrated a NCPM KTP-OPO emitting at 1.8 µm derived by a Nd:YAG=SrWO 4 Raman laser at 1180 nm. 14) In 2013, a 1625 nm signal light emitted from a NCPM KTA-OPO driven by a 1091 nm KTA Raman laser was obtained by Huang et al 15) In the same year, our group obtained a 2.1 µm NCPM KTA-OPO derived by a 1.3 µm Nd:YVO 4 laser.…”
mentioning
confidence: 99%